When is ambiguity-attitude constant? - Eichberger, Jürgen; Grant, Simon; Kelsey, David (CESifo working papers, 2012)
This paper studies how updating affects ambiguity-attitude. In particular we focus on the generalized Bayesian update of the Jaffray-Phillipe sub-class of Choquet Expected Utility preferences. We find conditions for ambiguity-attitude to be the same before and after updating. A necessary and sufficient condition for ambiguity-attitude to be unchanged when updated on an arbitrary event is for the capacity to be neo-additive. We find a condition for updating on a given partition to preserve ambiguity-attitude. We relate this to necessary and sufficient conditions for dynamic consistency. Finally we study whether ambiguity increases or decreases after updating. -- ambiguity ; generalized Bayesian update ; learning ; dynamic consistency ; Choquet Expected Utility
Keywords: Arbeitspapier; Graue Literatur